2021
DOI: 10.1001/jamanetworkopen.2021.33401
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Caffeine Consumption and Maternal Cardiometabolic Pregnancy Complications

Abstract: IMPORTANCEWomen are recommended to limit caffeine consumption to less than 200 mg per day based on risks to fetal health. Impacts of caffeine on maternal health remain unclear. OBJECTIVE To determine whether caffeinated-beverage intake and plasma caffeine and paraxanthine are associated with cardiometabolic complications in pregnancy (ie, gestational diabetes [GDM], preeclampsia, and gestational hypertension [GH]). DESIGN, SETTING, AND PARTICIPANTS This cohort study used data from a longitudinal pregnancy coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…[38][39][40][41] Therefore, one possible explanation for our results is the low caffeine intake of pregnant women in the included studies, leading to a lower proportion of pregnant women consuming moderate to high doses. 16,17,42 Although, as stated above, our results do not allow to draw a conclusion about causality, it is reasonable to speculate about possible mechanisms for the putative adverse effects of coffee or soft drink consumption on preeclampsia. Coffee contains several compounds such as kahweol, cafestol, chlorogenic acid, and trigonelline.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…[38][39][40][41] Therefore, one possible explanation for our results is the low caffeine intake of pregnant women in the included studies, leading to a lower proportion of pregnant women consuming moderate to high doses. 16,17,42 Although, as stated above, our results do not allow to draw a conclusion about causality, it is reasonable to speculate about possible mechanisms for the putative adverse effects of coffee or soft drink consumption on preeclampsia. Coffee contains several compounds such as kahweol, cafestol, chlorogenic acid, and trigonelline.…”
Section: Discussionmentioning
confidence: 58%
“…Pregnant women have been shown to signi cantly reduce their caffeine intake, especially coffee during pregnancy (37)(38)(39)(40). Therefore, one possible explanation for our results is the low caffeine intake of pregnant women in the included studies, leading to a lower proportion of pregnant women consuming moderate to high doses (14,15,41).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In addition, in vivo research showed that caffeine antagonizes adenosine receptor, which leads to higher release of epinephrine and therefore, enhanced insulin sensitivity ( Thong and Graham, 2002 ). Similarly, evidence from a recent cohort of pregnant women reported that caffeine intake reduced the risk for gestational diabetes mellitus (GDM) by decreasing blood glucose, C-reactive protein and C-peptide levels, and resulted in favorable lipid profiles ( Hinkle et al, 2021 ). Theanine consumption has also been shown to lower blood pressure ( Deka and Vita, 2011 ; Yoto et al, 2012 ) and reduce inflammation ( Sergi et al, 2017 ) both of which relate to a lower risk for cardio-metabolic diseases.…”
Section: Health Benefits Of Matchamentioning
confidence: 99%